Molecular mechanisms of versatile biological activity of interleukin-7 - Slyvka, A.V.; Okunev, O.V. (Вiopolymers and Cell, 2014)
As a result of immunological studies of the last 25 years it turned out that interleukin-7 (IL-7) is one of the most important regulatory cytokines of the immune system. It is special in many concerns. Having a strong impact on the development, proliferation and activation of immune cells it is, however, cannot be attributed to the classic cytokine-activators, like IL-2, as many types of cells require its presence at almost all stages of the development, and its spectrum of activities is impressive. The review aims to summarise the numerous data obtained on the IL-7 structure, biological activity, biological significance and features of functioning studied both in vitro and in vivo. We made the main emphasis on the IL-7 signal transduction pathways that determine the fate of T and B cells, as well as some other cells important for homeostasis of the organism. In our opinion, the analysis of literature in this field not only reveals a host of questions still unanswered, but also makes the path for perspective investigation more visible. У результаті імунологічних досліджень останніх 25 років показано, що інтерлейкін-7 (ІЛ-7) є одним з найважливіших регуляторних цитокінів імунної системи. Він чинить значний вплив на розвиток, проліферацію і активацію імунних клітин, однак не належить до класичних цитокінів-активаторів, як, наприклад, ІЛ- 2, оскільки багато типів клітин потребують його присутності майже на всіх стадіях розвитку, а спектр його активностей є вражаючим. Цей огляд має на меті узагальнити численні дані щодо структури ІЛ-7, його біологічної активності і особливостей функціонування in vitro та in vivo. Основний акцент зроблено на шляхах сигнальної трансдукції ІЛ-7, які визначають долю Т- і В-клітин, а також деяких інших клітин, важливих для підтримання гомеостазу організму. Аналіз літератури цієї сфери, на нашу думку, не лише виявив низку питань, які наразі не мають відповідей, але й окреслив напрямки для майбутніх досліджень. В результате иммунологических исследований последних 25 лет показано, что интерлейкин-7 (ИЛ-7) является одним из важнейших регуляторных цитокинов иммунной системы. Он оказывает значительное влияние на развитие, пролиферацию и активацию иммунных клеток, онднако не принадлежит к классическим цитокинам-активаторам, как, например, ИЛ-2, поскольку много типов клеток нуждаются в его присутствии почти на всех стадиях своего развития, а спектр его активностей впечатляет. Цель этого обзора состояла в обощении многочисленных данных по структуре ИЛ-7, его биологической активности и особенностям функционирования in vitro и in vivo. Основной акцент сделан на путях сигнальной трансдукции ИЛ-7, определяющих судьбу Т- и В-клеток, а также некоторых других клеток, важных для поддержания гомеостаза организма. Анализ литературы этой сферы, по нашему мнению, не только выявил ряд вопросов, на которые до сих пор нет ответов, но и очертил направления для будущих исследований.